Effect of antimicrobial activity of Eupatorium odoratum against clinical microbes - P, Ramesh; A, Subramani (International Journal of Scientific Research in Biological Sciences, 2018)
Traditional medicine is an important source of potentially useful compounds for the development of phytotherapetic agent. Antimicrobials of plant origin have enormous therapeutic potential in the treatment of infectious diseases while simultaneously migitigiting many of the side effects that are often associated with synthetic antimicrobials. In the present investigation suggested that the effect of antimicrobial activity of Epotorium odoratum against clinical microbes were performed. In the experiments of the test plant with different concentration of 25, 50, 75, and 100µl of aqueous and methanolic leaf extract were treated against the bacteria like Bacillus sp., E.coli, Entrococcus sp., K.pnemoniae and Staph. aureus and fungi such as Aspergillus flavus, A.niger. A.terreus, Penicillium sp. and Trichoderma sp. Performed respectively. However the antimicrobial properties of E.odoratum leaf with methanolic extract of higher concentration was excellent performance when compared to other solvent of aqueous extract of same plant. It can be concluded that the plant can be used to discover natural products that may serve as lead for the development of new biomedical applications.